Reconceptualising Poetry as a Multimodal Genre. Issue 3 (15th September 2015) - Newfield, Denise; D'abdon, Raphael
Abstract : This conceptual article theorises the role of poetry in English classrooms from a multimodal perspective. It discusses the gap between the practices of poetry inside and outside South African schools, particularly where English is taught as an additional language (EAL). The former is shown to be monomodal and prescriptive, while the latter is multimodal and exciting. The reconceptualisation of poetry as a multimodal genre is effected through the integration of multimodality and orality, two fields of study that deal with meaning making. The article attempts to bridge the divide between poetry in print and in performance. It begins with a critique of the current conceptualisation of poetry that underlies the EAL curriculum, practice, and assessment in South Africa. Through bringing multimodality and oral studies together complementarily, and building on empirical studies, an alternative conceptualisation of poetry is constructed. An English poem by a South African Xhosa‐speaking poet is used to demonstrate the curricular, pedagogic, and research implications of this alternative approach. The authors argue that poetry, if reconceptualised as a multimodal genre, can rejuvenate literacy, particularly in classrooms where English is not the first language of students.